Measurement of crack length in width tapered beam experiments. Issue 4 (16th February 2021) - Kempe, Michael D.; Morse, Joshua; Eafanti, Joshua; Julien, Scott E.; Wan, Kai-tak; Bruckman, Laura S.; Wang, Yu; French, Roger H.; Fairbrother, Andrew; Gu, Xiaohong; Napoli, Sophie; O'Brien, Gregory S.; et al.
Abstract: The width tapered beam method for measuring fracture toughness has been contemplated for use in measuring the adhesion of photovoltaic materials, is promoted by it being a viable method for use directly on modules rather than to engineered test specimens. However, precise determination of crack length is often difficult as failure often involves tendril formation, cavitation voids, and other plastic deformation at the crack front in addition to obfuscation by opaque materials. Because fracture energy varies as the square of crack length, imprecise crack tip length results in large measurement uncertainties. In this work, we develop a method to estimate the crack tip length using the relationship between the applied force and the displacement of the load frame. The crack tip is determined for every data point and can be defined from a calibration curve related to the amount of energy put into the beam, or from a theoretically idealized estimation. Once a calibration curve is set up and the equations programmed, the fracture energy as a function of position on the newly formed crack interface can be accurately estimated. The test additionally provides much easier analysis and insight into the joint failure through more precise knowledge of fracture toughness at each de-bonded area.